Acute Cholecystitis and Cholelithiasis Developed after Esophagectomy - Mitsuo Tachibana; Shoichi Kinugasa; Hiroshi Yoshimura; Dipok Kumar Dhar; Shuhei Ueda; Toshiyuki Fujii; Takeru Nakamoto; Ioannis Kyriazanos; Naofumi Nagasue (Canadian Journal of Gastroenterology)
BACKGROUND: Although the prevalence of gallstone disease after gastrectomy is reported to be high, its prevalence after esophagectomy is scarcely reported.